Rancang Bangun Sistem Informasi Audit Mutu Internal - Norfifah; Veri Julianto Julianto; Yunita Prastyaningsih (Indonesian Society of Applied Science, 2023)
Internal quality audits are conducted within the internal quality assurance system (SPMI) of higher education institutions to ensure compliance with SPMI standards and enhance a quality culture. Constraints in implementing internal quality audits include limitations in human resources, time, and costs, as well as the complexity of audit stages and documentation of audit findings. To address these challenges, a website-based information system has been designed using the waterfall method and the Unified Modeling Language (UML) approach, utilizing the PHP framework CodeIgniter and a MySQL database. The system aims to digitize and automate the implementation of internal quality audits to enhance effectiveness and efficiency. Additionally, it facilitates the management and storage of internal quality audit documents. For testing purposes, black-box testing is employed, consisting of 10 different test types. The testing results indicate a 90% success rate, while 10% of the data did not succeed due to the limitation of inputting text HTML.